PENDAMPINGAN DAN EDUKASI ANAK YATIM DALAM MENGHADAPI PANDEMI DI DESA SUKAHARJA - Priyadi, Wisia Joko; Syaiful, Syaiful; Aminda, Renea Shinta; Aminda, Annisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
The Covid-19 pandemic is a disaster for humanity, resulting in the deaths of thousands of people throughout the world, including in Indonesia, where it has had a huge impact on all levels of society, including orphans. The impacts can be direct, resulting in death, or secondary impacts that affect the community's economy. Community activities become limited, the wheels of the economy stagnate, which can reduce people's purchasing power and quality of life. The aim of implementing this KKN is to describe information on the importance of a healthy lifestyle for orphans in Sukaharja Village Rt. 04 RW.02, Ciomas District, Bogor Regency, so that later these orphaned children will be accustomed to clean and healthy living behavior both during the pandemic and during normal situations. The method used in this activity is the action research method (Action Research) with a participatory action program approach (Participatory Action Program) involving the target community group, namely 23 orphans. The educational material provided to orphans includes an introduction to COVID-19 and its symptoms, how to wash hands properly and correctly, how to use a mask correctly, how to physically distance, and how to adopt a clean and healthy lifestyle. Mentoring and educational activities are carried out by providing counseling on improving clean and healthy lifestyles in facing the pandemic using lecture methods, questions and answers with prizes, demonstrations and providing compensation. The results of the activities show that orphan children in Sukaharja village, RT. 04 RW. 02 can understand and be able to practice all the material presented.